Influence of the amount of loaded substrate on the energy efficiency of biogas production - Spodoba М. О.; Spodoba О. О. (Energy and Automation, 2025)
Today, humanity’s need for energy resources increases annually. The high cost of raw materials (oil, gas, fuel) leads to the need to search for alternative energy sources. Today, the fermentation of organic agricultural waste in biogas plants is one of the most environmentally friendly and economically advantageous solutions for obtaining energy from waste in the form of biogas. Along with this, a side effect of fermentation of organic waste is the production of valuable environmentally friendly fertilizers. However, the formation of biogas is a complex technological process, since in the process of methanogenesis it is necessary to maintain artificially created microclimate parameters. The influence of external factors such as temperature, acidity level pH, humidity, the presence of chemicals in the substrate can create negative consequences for the methane formation process, up to a possible complete loss of the loaded substrate in the biogas reactor. In order to avoid such negative situations, very strict requirements are established for the technological processes of biogas formation. Domestic and foreign scientists theoretically and experimentally establish optimal conditions for the methane formation process. Among them, the greatest attention is paid to maintaining the acidity level and maintaining the temperature according to the conditions of the technological process of biogas formation. According to the conditions of the technological process, biogas formation occurs in three temperature modes: psychrophilic, mesophilic and thermophilic, for which certain limits of temperature fluctuations are established. The greatest temperature differences occur during the loading of a new substrate. In order to avoid the occurrence of a critical temperature difference during loading and unloading processes, the condition of thermal equilibrium in the methane tank was considered. Based on theoretical calculations, the ratio between the mass of the substrate present in the reactor and the loaded fresh substrate was determined. Key words: methane tank, substrate temperature, biogas, thermal equilibrium, ratio, substrate heat capacity